2020
DOI: 10.1038/s41556-020-0481-4
|View full text |Cite
|
Sign up to set email alerts
|

Copper is an essential regulator of the autophagic kinases ULK1/2 to drive lung adenocarcinoma

Abstract: While the transition metal copper (Cu) is an essential nutrient that is conventionally viewed as a static cofactor within enzyme active sites, a nontraditional role for Cu as a modulator of kinase signaling is emerging. We discovered that Cu is required for the activity of the autophagic kinases ULK1/2 through a direct Cu-ULK1/2 interaction. Genetic loss of the Cu transporter Ctr1 or mutations in ULK1 that disrupt Cu-binding reduced ULK1/2-dependent signaling and autophagosome complex fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
155
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(177 citation statements)
references
References 64 publications
1
155
0
2
Order By: Relevance
“…In the presence of stressful conditions, like OS, malignancy and serum deprivation, autophagy will be triggered for the sake of adapting to structural remodeling induced by the stresses, which is achieved through the synthesis of greater amounts of energy and nutrients, removal of misfolded and long-lived proteins in cells, and the elimination of redundant or injured organelles together with the invasive microorganisms [ 10 ]. It has shown that Cu can induce autophagy [ [11] , [12] , [13] ]. Fang et al [ 14 ] have reported that CuSO 4 promotes autophagy occurrence and ROS exert an important role in autophagy induced by CuSO 4 in duck renal tubular epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of stressful conditions, like OS, malignancy and serum deprivation, autophagy will be triggered for the sake of adapting to structural remodeling induced by the stresses, which is achieved through the synthesis of greater amounts of energy and nutrients, removal of misfolded and long-lived proteins in cells, and the elimination of redundant or injured organelles together with the invasive microorganisms [ 10 ]. It has shown that Cu can induce autophagy [ [11] , [12] , [13] ]. Fang et al [ 14 ] have reported that CuSO 4 promotes autophagy occurrence and ROS exert an important role in autophagy induced by CuSO 4 in duck renal tubular epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the authors also found that copper deficiency decreases the formation of autophagy-initiating phagophores, which contain important ULK1/2 downstream targets (Figure 1). Finally, when expressing an ULK1 mutant that lacks the histidine-methionine copper binding sequence, Tsang et al observed reduced ULK1 kinase activity as well as a significantly reduced autophagic flux in response to amino acid deprivation [7]. Altogether, these findings are compatible with the conclusion that copper binding to ULK1/2 is necessary and sufficient to increase autophagic flux.…”
mentioning
confidence: 70%
“…In direct agreement with this vison, Tsang et al found that two pro-autophagic kinases, Unc-51 like autophagy activating kinases 1 and 2 (ULK1, ULK2) possess MEK1-like copper-binding sequences [7]. In vitro, ULK1 and 2 do not bind iron or zinc, but copper, which dose-dependently increases their kinase activity.…”
mentioning
confidence: 77%
“…Regulated copper homeostasis is fundamental in mammalian cells. Copper is an essential substrate for cell growth and differentiation, a cofactor of many enzymes and has even recently been identified as being necessary for ULK1 and ULK2 signalling, linking it to autophagy activity ( Kim et al, 2008 ; Tsang et al, 2020 ). Therefore, it is unsurprising there are severe adverse effects associated with copper dyshomeostasis.…”
Section: Discussionmentioning
confidence: 99%